# Chapter 6 Page no. 224 34.

Find two positive numbers whose sum is 15 and the sum of whose squares is minimum. Solution- Let one of the numbers be x. Then the other number is (15 –x). Let S(x) denotes the sum of the squares of these numbers. Then S(x) = x2 + (15 – x)2 = 2x2 – 30x + 225 Or { ( ) ( ) . Also S”( ) therefore by second derivative test, x = and is the point of local

Now S’(x) = 0 gives x =

minima of S. Hence the sum of squares of numbers is minimum when the numbers are

Remark- Proceeding as in Example 34 one may prove that the two positive numbers, whose sum is k and the sum of whose squares is minimum, are and Page no. 223 23. Find the approximate value of f(3.02), where f(x) = 3x2 + 5x + 3. Solution- Let x = 3 and x = 0.02. Then f(3. 02) = f(x + x) = 3(x + x)2 + 5(x + x) + 3 Note that y = f(x + x) – f(x). Therefore f(x + x) = f(x) + y = f(x) + f’(x) x Or f(3.02)  (3x2 + 5x + 3) + (6x + 5) x = (3(3)2 + 5(3) + 3) + (6(3) + 5) (0.02) = (27 + 15 + 3) + (18 + 5) (0.02) = 45 + 0.46 = 45.46 Hence, approximate value of f(3.02) is 45.46. V.P.M (Book) (as x = 3, x = 0.02) (as dx = x)

E. 2001. Maximum value of (A) (B) 0 (C) (D) 1 Ans. x  R f’(x) = ae ax – ae.T. where: (A) x < 0 (D.e. if i.C. if i. (C): Let f(x) =  f’(x) = f’(x) = 0   in [2.20.e.e.e. (A): Given f(x) = eax + e-ax. P. if i. if aeax – ae-ax < 0 eax > e-ax ( a < 0) e2ax > 1 2ax > 0 x<0 . 2002) 1 – log x = 0 x=e f”(x) =    f”(e) = f(x) is maximum at x = e Maximum value of f(x) = = <0 = 24. the function f(x) = eax + e –ax is monotonically decreasing for all values of x.E.P. Roorkee 1992) (B) x > 0 (C) x < 1 (D) x > 1 Ans. ) is : (M.ax  f is monotonically decreasing if f’(x) < 0 i.e. if i. If a < 0.

E. 3 (Karnataka C. (D): Here f(x) = 2x3 – 15x2 + 36x + 4 f’(x) = 6x2 – 30x + 36 Now f’(x) = 0  6x2 – 30x + 36 = 0   f”(2) = .T.2001)  f is maximum at x = 2 27.25. one value of x is equal to: (A) – (B) . The function f(x) = 2x3 – 15x2 + 36x + 4 is maximum at: (A) x = 3 (B) x = 0 (C) x = 4 (D) x = 2 Ans. When the function f(x) = sin 2x (1 + cos 2x) has a maximum.6 < 0 f” (3) = 6 > 0 x2 – 5x + 6 = 0 x = 2.